2006
DOI: 10.1093/eurheartj/ehl113
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing familial hypercholesterolaemia: the relevance of genetic testing

Abstract: Despite the use of stringent clinical criteria to define FH patients, two cohorts could be identified within our study population, namely those patients with and those without an LDLR mutation. Our findings suggest that among those without an LDLR mutation, patients with other causes of dyslipidaemia may be present. These observations underline the relevance of genetic testing in FH for clinical practice, for screening purposes, and for research involving these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…However, it has been suggested that the diagnosis of FH should be based on the identification of the genetic defect because statin therapy needs to be initiated in young carriers of a LDLR mutation even if their plasma LDLc is normal. 27 However, no general agreement exists on this approach because the risk of CHD is about the same in phenotypically defined FH patients with or without mutation in the LDLR gene. 28 The clinical benefit of the genetic diagnosis over the careful monitoring of LDLc levels, which is required anyway, is therefore questionable.…”
Section: Ldl Receptor Genementioning
confidence: 99%
“…However, it has been suggested that the diagnosis of FH should be based on the identification of the genetic defect because statin therapy needs to be initiated in young carriers of a LDLR mutation even if their plasma LDLc is normal. 27 However, no general agreement exists on this approach because the risk of CHD is about the same in phenotypically defined FH patients with or without mutation in the LDLR gene. 28 The clinical benefit of the genetic diagnosis over the careful monitoring of LDLc levels, which is required anyway, is therefore questionable.…”
Section: Ldl Receptor Genementioning
confidence: 99%
“…Comparison of individuals with and without LDLR mutation in this cohort showed significant differences as published earlier by Van Aalst-Cohen et al: patients with FH without an LDLR mutation had higher triglyceride levels (1.71 versus 1.39 mmol/L), body mass index (25.6 versus 24.7 kg/m 2 ), and systolic blood pressure (137 versus 133 mm Hg) and were more likely to have ever smoked (79.5% versus 68.7%), whereas patients with FH with an LDLR mutation had higher low-density lipoprotein cholesterol levels (8.18 versus 6.61 mmol/L). 25 Successfully genotyping for APOE was assessed in 2061 patients of whom 1150 had an LDLR mutation. The polymorphisms at positions 112 and 158 were in Hardy-Weinberg equilibrium both in the whole population and in the group with an LDLR mutation.…”
Section: Resultsmentioning
confidence: 99%
“…All described variants will be submitted to the following public variant database Leiden Open Variation Database (LOVD) 3 (http://databases.lovd.nl/ shared/genes/).…”
Section: Discussionmentioning
confidence: 99%
“…1 By virtue of the elevated LDL-C levels, FH results in lipid accumulation in the arterial wall and as a consequence accelerated atherosclerosis. 2,3 If left untreated, 50% of male and 30% of female heterozygous FH patients will develop CAD before 60 years of age. 4 The age of onset and severity of CAD varies considerably between FH patients, even among individuals who share an identical gene defect.…”
Section: Introductionmentioning
confidence: 99%